Spatial Distribution and Trends of Waterborne Diseases in Tashkent Province - Veluswami Saravanan Subramanian; Min Jung Cho; Siwei Zoe Tan; Dilorom Fayzieva; Christian Sebaly (University Library System, University of Pittsburgh, 2017)
Introduction: The cumulative effect of limited investment in public water systems, inadequate public health infrastructure, and gaps in infectious disease prevention increased the incidence of waterborne diseases in Uzbekistan. The objectives of this study were: (1) to spatially analyze the distribution of the diseases in Tashkent Province, (2) to identify the intensity of spatial trends in the province, (3) to identify urban-rural characteristics of the disease distribution, and (4) to identify the differences in disease incidence between pediatric and adult populations of the province. Methods: Data on four major waterborne diseases and socio-demographics factors were collected in Tashkent Province from 2011 to 2014. Descriptive epidemiological methods and spatial-temporal methods were used to investigate the distribution and trends, and to identify waterborne diseases hotspots and vulnerable population groups in the province. Results: Hepatitis A and enterobiasis had a high incidence in most of Tashkent Province, with higher incidences in the eastern and western districts. Residents of rural areas, including children, were found to be more vulnerable to the waterborne diseases compared to other populations living in the province. Conclusions: This pilot study calls for more scientific investigations of waterborne diseases and their effect on public health in the region, which could facilitate targeted public health interventions in vulnerable regions of Uzbekistan.